Mobile internet security : first International Symposium, MobiSec 2016, Taichung, Taiwan, July 14-15, 2016, Revised selected papers /: first International Symposium, MobiSec 2016, Taichung, Taiwan, July 14-15, 2016, Revised selected papers. (2018) - Unknown
No abstract available